Vulnerability and Resilience Embedded in Discourses: Literature, Media, and Actors' Cultural Knowledge in German and Polish River Regions - Thorsten Heimann; Anna Barcz; Gabriela Christmann; Kamil Bembnista; Petra Buchta-Bartodziej; Anna Michalak (Space and Culture, 2021)
The sociology of knowledge approach to discourse assumes that cultural knowledge—and thus cultural spaces—are generated and shared through discourse. Actors' shared perceptions of vulnerability and practices to create resilience should be interrelated with knowledge provided by the relevant discourses of local and historical influence. However, these assumptions have not been thoroughly examined. This study compares river-related knowledge (concerning human–river relationships: ecocentric and anthropocentric perspectives) in the German and Polish literary canons, with knowledge provided in the relevant public media and the shared knowledge of local populations in flood-prone city districts along the Odra River. It concludes that actors' river-related knowledge interrelates with the knowledge produced by national and regional discourses and that culturally shared ideas of vulnerability and resilience are discursively embedded.
Keywords: 710; vulnerability; resilience; floods; discursive embeddedness; sociology of knowledge approach to discourse